The problem of the transcendental subject and its justification in Kant’s critical philosophy - Rovbo, Margarita V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The essence of the problem of transcendental subject in Kant’s philosophy is considered. The special place of this subject in Kant’s transcendental critical project is defined. The author takes into account not only Kant’s theoretical philosophy, within frame of which the transcendental subject has been first stated, but also practical philosophy, in which the potential and purpose of this subject most completely fulfil. The concept of the transcendental subject is not identical to the subject of thinking, as well as it is not a vestige of pre-Kantian metaphysics. The concept of the transcendental subject is complicated refraction of different representations from rational psychology, metaphysics of substance and critical project in itself.
Keywords: transcendental subject; substance; substantial; spontaneity; rational psychology; Kant’s criticism; history of philosophy